2007
DOI: 10.2116/analsci.23.1159
|View full text |Cite
|
Sign up to set email alerts
|

Basic Design and Synthesis of Sulfonated Contrast Agents for Magnetic Resonance Imaging Based on Gadolinium Complexes

Abstract: Magnetic resonance imaging (MRI) is a powerful noninvasive diagnostic technique that can differentiate normal tissue from diseased tissue and lesions. Magnetic resonance angiography (MRA) is a specialized MRI technique of gradually increasing importance that can provide angiography and can assess angiogenesis, blood volume and blood flow. [1][2][3][4] Various contrast agents based on gadolinium ion (Gd 3+ ) complexes have been developed to enhance the MRI signal intensity and to improve the contrast-to-noise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The lipophilic residue facilitates noncovalent interaction of MS-325 to the lipid binding sites of HSA and significantly augments its plasma half-life. Hydrophilic−lipophilic balance (HLB) of the Gd(III) complex is a vital factor controlling the plasma half-life and elimination from the organism . To augment the lipophilicity of the [Gd(TTDA)(H 2 O)] 2− , we introduce lipophilic residues such as cyclobutyl and benzyl groups on the carbon backbone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lipophilic residue facilitates noncovalent interaction of MS-325 to the lipid binding sites of HSA and significantly augments its plasma half-life. Hydrophilic−lipophilic balance (HLB) of the Gd(III) complex is a vital factor controlling the plasma half-life and elimination from the organism . To augment the lipophilicity of the [Gd(TTDA)(H 2 O)] 2− , we introduce lipophilic residues such as cyclobutyl and benzyl groups on the carbon backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophilic-lipophilic balance (HLB) of the Gd(III) complex is a vital factor controlling the plasma half-life and elimination from the organism. 74 To augment the lipophilicity of the [Gd(TTDA)(H 2 O)] 2-, we introduce lipophilic residues such as cyclobutyl and benzyl groups on the carbon backbone. The octanol-water distribution ratio, K O/W , is the accepted physicochemical property measuring the hydrophobicity of Gd(III) complexes.…”
Section: Resultsmentioning
confidence: 99%
“…16). 127 The lipophilicity and the hydrophilicity of the Gd(III) complexes were investigated in order to increase the plasma half-life by binding to human serum albumin. The results showed that KMR-Sulfo5 has a relaxivity r 1 of 5.9 mM À1 s À1 and a long plasma half-life of 25.7 min.…”
Section: A Non-covalent Binding To Plasma Proteinsmentioning
confidence: 99%